1995
DOI: 10.1007/bf00203364
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound examination of the small bowel: comparison with enteroclysis in patients with Crohn disease

Abstract: US, therefore, seems to be a reliable method in the workup of patients suspected of having inflammatory small bowel disease. Thereby, US probably can select patients for SBF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(42 citation statements)
references
References 12 publications
3
39
0
Order By: Relevance
“…[11][12][13]15,16,[20][21][22][23] One study involved a pediatric population. 16 One meta-analysis and 1 systematic review were also considered.…”
Section: Methodsmentioning
confidence: 99%
“…[11][12][13]15,16,[20][21][22][23] One study involved a pediatric population. 16 One meta-analysis and 1 systematic review were also considered.…”
Section: Methodsmentioning
confidence: 99%
“…In this regard, interobserver agreement between sonographers with variable experience in bowel US has been reported in a few preliminary studies showing satisfactory results, but a learning curve for this technique is still lacking. 15,23,24 This is probably one of the main reasons why intestinal US is, in clinical practice, still regarded with scepticism by many clinicians and radiologists. However, when discussing the limits and accuracy of US assessment in Crohn's disease, we should bear in mind that most results are derived from studies dating from the 1990s and that the technical evolution of US equipment has probably now increased the accuracy of US detection of Crohn's disease.…”
Section: Early Evaluation Of Patients With Suspected Crohn's Diseasementioning
confidence: 98%
“…3 Of particular interest are comparative prospective studies, performed in unselected groups of patients, which have shown that intestinal US may diagnose Crohn's disease with a sensitivity ranging from 67 to 96% and a specificity ranging from 79 to 100%. [8][9][10][11][12][13][14][15][16][17][18][19] It should, however, be borne in mind that the diagnostic accuracy of these studies is based on investigations that differed in terms of design, population characteristics and reference standards. Most of these results were obtained from studies that included patients with a previous diagnosis of Crohn's disease but lacked a control population, and it is therefore difficult to achieve a comprehensive evaluation of sensitivity and specificity of the US.…”
Section: Early Evaluation Of Patients With Suspected Crohn's Diseasementioning
confidence: 99%
“…Also, having a high negative predictive value, it can rule out CD in subjects with non-specific gastrointestinal symptoms and normal biomarkers such as CRP and fecal calprotectin [51,52]. It has been proven that intestinal US combined with colonoscopy has the highest diagnostic accuracy and is the most cost efficient method compared to MRI for the assessment of patients with suspected CD [53].…”
Section: Crohn's Diseasementioning
confidence: 99%